Anomalous Walker circulations associated with two flavors of the Indian Ocean Dipole - Tomoki Tozuka; Satoru Endo; Toshio Yamagata (Geophysical Research Letters)
Abstract The Walker circulation is the key component of the atmospheric zonal circulation in the tropics. In this study, it is shown that anomalous Walker circulations associated with two types of the Indian Ocean Dipole (IOD) are remarkably different. During a positive canonical IOD with negative (positive) sea surface temperature (SST) anomalies in the eastern (central to western) tropical Indian Ocean, a single‐cell anomalous Walker circulation forms over the Indian Ocean. On the other hand, a double‐cell anomalous Walker circulation with a rising branch in the central Indian Ocean is formed during a positive IOD Modoki, which is associated with positive (negative) SST anomalies over the central (eastern and western) tropical Indian Ocean. The above anomalous Walker circulations are found to develop as part of positive ocean‐atmosphere feedback. Furthermore, the above difference in the anomalous Walker circulation may affect the biennial tendency of the IOD.